Undergraduates in a second language : challenges and complexities of academic literacy development - Leki, Ilona (New York : Lawrence Erlbaum Associates, 2007)
This is the first book-length study of bilingual, international, and immigrant students in English writing courses that attempts to fully embed their writing experiences within the broader frame of their personal histories, the human context of their development, and the disciplinary contexts of their majors. It addresses the questions: How useful are L2 writing courses for the students who are required to take them? What do the students carry with them from these courses to their other disciplinary courses across the curriculum? What happens to these students after they leave ESL, English, or writing classes? Drawing on data from a 5-year longitudinal study of four university students for whom English was not their strongest/primary language, it captures their literacy experiences throughout their undergraduate careers. The intensive case studies answer some questions and raise others about these students' academic development as it entwined with their social experiences and identity formation and with the ideological context of studying at a U.S. university in the 1990s.--Cover, p. [4]
"You need really understand": an undergraduate in engineering -- "Don't have easy": nursing in L2 -- "Suddenly you get recognized": the power of community -- "Yuko can handle intimidation": becoming a social worker -- University literacy -- Social and ideological contexts of literacy developments.
Includes bibliographical references (pages 309-319) and indexes.
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching